Ethical Accounting in a Global Context : The Role of Culture in Entrepreneurial Decision-Making - Ali, Md. Mokshud; Wafik, H M Atif; Hossain, Zakir; Nobi, Md. Nur; Moni , Sharmin Akter; Kabir, Irfanul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study examines how ethical accounting procedures and culture interact in the setting of entrepreneurship. It highlights how important cultural factors—like individuality, collectivism, and avoiding ambiguity—are to moral decision-making in accounting. A qualitative method that makes use of secondary data emphasizes how organizational behavior and ethical frameworks are shaped by cultural values. Key findings show that whereas collectivist cultures encourage collective responsibility in ethical behaviors, high uncertainty avoidance cultures impose more stringent ethical standards. One important element that improves ethical behavior and stakeholder trust is the incorporation of corporate social responsibility or CSR. The study also addresses the moral dilemmas raised by globalization and technology breakthroughs, which call for cultural competency in negotiating a variety of moral terrains. Entrepreneurs are advised to set clear ethical principles, promote an ethical business culture, and provide cultural sensitivity training. Businesses may successfully negotiate the challenges of moral accounting decision-making by cultivating cultural sensitivity and placing a high priority on moral principles, thereby supporting ethical and sustainable entrepreneurship in a globalized world.